REVIVING ECONOMIC THOUGHT BY MANNAN PERSPECTIVE - Amiruddin, Muhammad Majdy; Ismail, Muhammad; Hasim, Hasanuddin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
The reviving of modern economic theory is usually stated starting from the publication of Adam Smith’s The Wealth of Natoins, in 1776, although other thinkers who first also gave no small contribution. The main idea put forward by Adam Smith is that competition between various suppliers of goods and buyers will produce the best possibilities in the distribution of goods and services because it will encourage everyoe to do the specialization and increase in capital so that it will produce more value with a permanent workforce. From the Islamic perspective, there are several names that commonly known such, Baqir, Umar Chapra, and Mannan. The purpose of this research is to explore the revival economic though by Abdul Mannan. This research adapts content analysis method, which is a researcher conducts a discussion of the contents of written or edition information in the mass media. The data analysis techniques of this scientific work use literature study techniques, comparative, induction, and deduction. The study began by collecting literature data from Muhammad Abdul Mannan’s Concept of Thinking about the Development of Modern Era Islamic economics and Modern Era Islamic Economic concepts in general, (researchers only participated in the discussion). Then proceed with the interpretation that researchers try to understand Muhammad Abdul Mannan’s thoughts about the Development of Islamic Economics in the Modern Era. The result of this reseacrh indicates that the revival of Islamic thought by determining basic economic functions that simply cover three functions, namely consumption, production and distribution. Those basics are rooted by Five basic principles rooted in Shariah for basic economic functions in the form of consumption functions are the principles of righteousness, cleanliness, moderation, benefit and morality